Knowledge management in Interreg cross-border cooperation: A project perspective - Susanne Marx (Hochschule Stralsund, Stralsund Information Management Team (SIMAT), 2018)
The management of knowledge in projects delivers benefits, while the im-plementation of knowledge management is challenged by (project-specific) issues. Based on practice in interorganizational, cross-border projects funded by the Interreg South Baltic Programme (SBP), this paper analyses the potential value and hindrances of knowledge management in projects funded within Interreg programs. The SBP mentions repeatedly "Transfer of knowledge and exchange of good practices" as an example activity in the program manual (Interreg South Baltic Programme 2016b, pp. 13, 25, 34, 38), however, dedicated knowledge management processes, tools or plans are not part of the com-pulsory application for funding nor its assessment. Knowledge management (KM) can provide value at different levels: to individuals, project partner organisations, the entire programme and even cross-programme as well as other project stakeholders. While KM can support strategy towards building competitive advantage in the programme region, KM processes can enhance the efficiency of project implementation. Worth noting is the impact of KM on individual motivation both for joining a project and for contributing to knowledge exchange. [...]
Keywords: M16; O13; O22; Z39; 650; Project Knowledge Management; Interreg; EU project; Inter-organizational Cooperation; Cross-border Cooperation; Knowledge Management Framework; Knowledge Management Processes; Project Knowledge Facilitator